Efektifitas Perangat Pembelajaran Inkuiri Terintegrasi Kearifan Lokal Terhadap Keterampilan Berpikir Kritis Mahasiswa - Hunaepi Hunaepi; Laras Firdaus; Taufik Samsuri; Endang Susantini; Raharjo Raharjo (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2020)
This study aims to improve the ability of the inquiry learning tool integrated with local wisdom in improving students' critical thinking skills. There were four classes of experiments to determine entitlements in research results, which were also designed as pretest-posttest groups. The sample in this study were 100 students, who were divided into four groups using saturated sampling technique. The critical thinking skills test consisted of 6 items which were declared valid. The results showed that the thinking skills of students before and after learning the software were significantly different (p <0.05). These results indicate that the learning tools developed effectively improve students' critical thinking skills, although the average increase in each indicator is in the medium category. This condition indicates that for further research it is necessary to develop an inquiry model that is integrated with local wisdom.